Nanoemulsion of Curcuma longa Extract Improves the Developmental Process in High Glucose-Induced Zebrafish (Danio rerio) Embryos - Devi Maya Arista; Rizki Amelia; Husnul Khotimah; Subandi Subandi; Fatnuraini Priyahita; Nabila Fathir; Nastyazka Subakti; Hafizhah Dini Syarafina (JURNAL INFO KESEHATAN, 2025)
Gestational diabetes mellitus (GDM) is hyperglycemia during pregnancy, which can increase oxidative stress and reactive oxygen species (ROS). This oxidative stress can adversely affect fetal developmental processes, including body length, ocular development, blood flow, and heart rate. Curcuma longa extract, containing curcumin, has been shown to possess antidiabetic and antioxidant properties. Nanoemulsions have demonstrated efficacy in enhancing the pharmacokinetics and pharmacodynamics of herbal compounds. This study aimed to evaluate the effect of a nanoemulsion of Curcuma longa extract on body length, ocular apoptosis, blood flow, and heart rate in zebrafish (Danio rerio) embryos exposed to high glucose concentrations. Zebrafish has many benefits as it has 70% orthologous genes with humans, high fecundity, and rapid embryogenesis. Nanoemulsions were prepared using the self-nanoemulsifying drug delivery system (SNEDDS) technique. Embryos were allocated to five groups: control, 3% glucose, and 3% glucose with 1.25, 2.5, or 5 µg/mL nanoemulsion of Curcuma longa extract. The results showed that a 1.25 µg/mL nanoemulsion of Curcuma longa extract reduced phosphoenolpyruvate carboxykinase (PEPCK) expression, increased body length, and mitigated developmental process disorders by decreasing ocular apoptosis and maintaining blood flow and heart rate in high glucose-induced zebrafish embryos. These findings suggest that a nanoemulsion of Curcuma longa extract may have potential therapeutic applications in managing the adverse effects of hyperglycemia on fetal development in GDM.